Granulomatous Pneumocystis Jiroveci Pneumonia Associated with Immune Reconstituted HIV - Natasha F Sabur; Margaret M Kelly; M John Gill; Martha D Ainslie; Sachin R Pendharkar (Canadian Respiratory Journal)
Pneumocystis jiroveci pneumonia uncommonly presents with pulmonary nodules and granulomatous inflammation. An unusual case of granulomatous P jiroveci pneumonia in an HIV patient with a CD4+ lymphocyte count of greater than 200 cells/mm3, occurring in the context of immune reconstitution with highly active antiretroviral therapy, is described. The case highlights the importance of establishing this diagnosis to institute appropriate therapy.